Supplementation with humic substances affects the innate immunity in layer hens in posfasting phase (2016)
Objective. Asses the effect of supplementation with Humic substances (HS) over some innate immunity parameters (serum bactericidal activity, phagocytosis, bacterial agglutination, respiratory burst and lisozyme activity) in phase after fasting of layer hens. Materials and methods. 120 posfasting phase Hy Line Brown layer hens were taken which were distributed into four groups: The first and the second were supplemented with 0.1 and 0.2% of HS, respectively. The third group was supplemented with 0.25 mg/kg on levamisole hydrochloride and fourth group have no supplementation; during sixty days period. Blood samples were collected on 8th, 30th and 60th of experiment day. Results. The phagocytic index and respiratory burst increased significantly at day 30th in HS supplemented groups. Alike, serum bactericidal activity and lisozyme activity improved on 8 th day, nevertheless, changes were no evident latter. The bacterial agglutination was high in supplemented groups evaluated at everyone times. Conclusions. Results showed that HS behave as immunostimulant in the early phase after fasting layer hens.